Social network usage, self-esteem, and irrational consumption online among chinese college students: a mediation model - Zhou, Huiquan; Li, Mei (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
With the development of e-commerce in recent years, online consumption and the resulting phenomenon of irrational consumption online have gradually attracted research attention. This paper explored to what extent self-esteem and social media usage influence Chinese young consumers’ irrational consumption behavior. A total of 1504 Chinese college students over 30 provinces were recruited by convenience sampling and answered an online survey between August 2019 and May 2020. The Bootstrap method was used to examine the mediating effects of excessive use of social media on the relationship between self-esteem and irrational consumer behaviors. Results showed that both self-esteem and social media usage have a direct and significant relationship with irrational consumption; and the degree of social media overuse mediates the relationship between self-esteem and irrational consumption. Such results imply that an individual's self-esteem can influence his/her irrational consumption behavior by influencing the extent of his/her social media usage. The findings have significant implications for developing programs that aim to promote healthy financial behavior among young people in the digital age. At the same time, the study also makes theoretical contributions to the field of consumer behavior in the cyber era.